POTENSI ARTIKEL UNTUK DIMUAT DI JURNAL NASIONAL DAN INTERNASIONAL Studi Kasus Di Fakultas Sains Dan Teknologi (Dalam Rangka Pengembangan Manajemen Jurnal Pendidikan Matematika UIN Sunan Kalijaga/JPMSUKA) - Ibrahim, Ibrahim (Idaarah: Jurnal Manajemen Pendidikan, 2019)
This study aims to find out how the potential articles in the Mathematics Education Study Program at the Faculty of Science and Technology UIN Sunan Kalijaga to be published in the national journal of accreditation and international journal. The type of research used in this study is qualitative research with a case study approach. The sample in this study are 25 articles selected from a total of 247 articles in the population. The research instruments used in this study include article rating scales, interview guidelines, and observation guidelines. Data triangulation is done to test the validity of the data obtained. The data analysis technique used in this study is descriptive quantitative and qualitative descriptive. The results showes that (1) articles written by students of the Mathematics Education Study Program at UIN Sunan Kalijaga Yogyakarta have high potential to be published in reputable national journals and international journals in the abstract, preliminary aspects, aspects of research methods, outcome aspects, discussion, and conclusions, as well as aspects of language and display format; (2) articles written by students of the Mathematics Education Study Program at UIN Sunan Kalijaga Yogyakarta have the potential to be published in reputable national and international journals in the library aspect.